Labor Wage System Viewed From Muamalah Fiqh Principles and Law No. 13 of 2003 Concerning Employment - Raden Nurhayati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Wages or ijarah are a contract to take advantage by way of replacement (payment). In other words, ijarah is the ownership of the services of a mu'ajiir by a mustajiir, as well as the owner of the assets of the mustajiir by a mu'ajiir. The issue of wages is emphasized by the Hadith of the Prophet Muhammad SAW presented by Abi Said Al Khuduri, RA., which contains “ Whoever hires an ajiir should mention the wages or payments. Another hadith further says from Ibn Umar RA that the Messenger of Allah said that “ Give workers their wages before their sweat dries (HR. Ibn Majah). Workers/laborers have the right to earn income that can meet their more decent and more prosperous livelihood, so the government has established a wage policy that protects workers/laborers. Based on the initial analysis, there is harmony between the wage systems in accordance with Law no. 13 of 2003 with a muamalah principle view. It would be even better if the study were continued in more depth so that the similarities and differences would be truly clearly described.